Basis of bone strength vs. bone fragility: A review of determinants of age-related hip fracture risk - Đonić Danijela; Milovanović Petar; Đurić Marija (Srpski Arhiv za Celokupno Lekarstvo, 2013)
The burden of hip fractures in elderly population has been growing worldwide. A particular focus has been directed towards identifying persons at high risk of fracture. However, bone mineral density (BMD), which is currently used in clinical settings as an indicator of risk of age-related fracture, cannot explain all fracture cases in the elderly. In fact, the risk of hip fractures in the elderly is associated with numerous bone features that degrade bone strength. This review focuses on complexity of bone features that could account for increased bone fragility in advanced age. Besides a decrease in BMD, various macroscopic and microscopic structural parameters, as well as the material of which the bone is composed, are subject to age-related changes. Therefore, in order to have a more thorough assessment of the fracture risk, it is essential to provide integrative approaches that combine BMD measure with other relevant bone features. [Projekat Ministarstva nauke Republike Srbije, br. 45005]